Smart Beta Investing: An Alternative Investment Paradigm in Emerging Indian Equity Market - Monga, Reema; Aggrawal, Deepti; Singh, Jagvinder (Organizations and Markets in Emerging Economies, 2022)
This paper fundamentally looks at the novel concept of Smart Beta investing in constructing a more efficient and well-diversified alternative investment. Smart beta has been a popular investment philosophy, although emerging countries have been slower to adopt and execute it. In this way, the study investigates the existence, performance, and robustness of smart beta strategies in a divergent financial market. Moreover, it is an initial attempt to integrate the framework of stock selection and stock weighting to construct and test smart beta strategies against the traditional Indian market benchmark (S&P BSE 500). The findings show that smart beta investing results in a better risk-return profile on an absolute and risk-adjusted basis. Furthermore, the results demonstrate the consistency and robustness of smart beta strategies in different market conditions and display their outperformance even in bearish market conditions.
Keywords: Active and Passive investment; Factor exposure; Idiosyncratic risk; Indian equity market; Innovative investment; Risk parity; Smart Beta Investing